A Narrative Review of the Understanding of Post-operative Wound Care in Ayurveda Literature - V, Sreedevi; Asutkar, Sheetal (Biomedical Sciences and Clinical Medicine, 2025)
The intricacies of meticulous wound healing or Vrana Ropana has been comprehensively reviewed and diligent attempts have been made at understanding the mechanisms involved in optimal wound healing via the comprehensive explanations of both Ayurveda and contemporary literature to achieve a much sought after integration of post-surgical wound care. Post-operative wound care protocols are regularly and rigorously updated as the burdens of post-surgical wound complications are on the rise. A thorough understanding of surgical wounds, stages of wound healing and optimal wound care along with identifying red flags indicating susceptibility to complications. Classic Ayurveda documents describe specialised wound care strategies associated with the use of surgical instruments as well as para-surgical therapy related to therapeutic cautery, caustic cauterization as well as wounds caused by leeches in blood-letting therapies. This presents an opportunity for the integration of those strategies with conventional knowledge in present-day surgical care which could potentially increase the efficacy and precision of wound care by minimising post-operative complications. Databases like PubMed and Scopus were searched using keywords including Sadyo Vrana, Vrana Ropana, Sastra Karma, post-operative wound care, post-surgical care and Ayurvedic methods for preventing surgical site infections. Comparison of types of wounds, mechanisms of healing and post-operative care according to evidence-based Ayurveda principles with relevant contemporary literature potentially increase understanding of what is required for a holistically integrated care plan which can help achieve uneventful post-operative surgical wound healing. To that end, it is necessary both to understand the conventional care of surgical wounds and to compare that with the existing care of post-surgical wounds as well as to identify new scopes of care including highlighting areas of bridging integrative approaches to reduce post-operative complications and to attain optimum wound healing.